Introduction to the Special feature: Lost in the ecosystem - Very, Philippe; Tournois, Nadine (Management international / International Management / Gestiòn Internacional, 2024)
The concept of ecosystem is used, from the local to the international level, to analyze the notions of balance and resilience. The introductory research note of this dossier proposes a reflection on this central concept of ecosystem used by economists/managers on the one hand and by biologists/ecologists on the other. The study shows the confusion born from this double appropriation and the need to clarify the meaning of the concept when it is used by researchers.